Of hoaxes and homicide - Hastings, Anastasia (Hastings, Anastasia. Dear Miss Hermione mystery, 2024)
"The second in the delightful Dear Miss Hermione mystery series from Anastasia Hastings--when you represent the best-loved Agony Aunt in Britain, fielding questions from both irate housekeepers and heartbroken mothers is par for the course... "Dear Miss Hermione--what is a mother to do?" Sensible Violet Manville and her very ladylike half-sister Sephora are absolutely bored, thank you very much. And though neither of them would ever admit it aloud, they're missing the thrill of playing detective. So when Violet receives a letter from "A Heartbroken Mother" sent to her alter-ego, the Agony Aunt known to the world only as Miss Hermione, her pulse can't help but quicken. The daughter in question has gotten caught up in a cult: the Hermetic Order of the Children of Aed. Rumors of human sacrifices, mystical doings, and a ghost in the ruined Alburn Abbey where the Children pray have gripped the public consciousness, helped along by a series of novels about the group, written by the mysterious Count Orlando, and clearly this girl has fallen prey. Miss Hermione's investigation soon collides with very real life when Violet discovers that the runaway daughter in question is Sephora's dearest friend Margaret. Violet sets off to the Children's compound in Nottingham to convince her to return to London. But with the dashing-but-frustrating Eli Marsh running around and a member of the Children found poisoned to death, Violet and Sephora--along with their ever-trusty housekeeper Bunty--may have more intrigue than they can manage"--